UNDERSTANDING RELIGIOUS VIOLENCE IN INDONESIA: Theological, Structural and Cultural Analyses (State Islamic University (UIN) of Sunan Ampel Surabaya, 2012)
Lately Indonesia is facing a lot of tremendous experience about religious violence. Indonesian Islam which is previously assumed as peaceful religion is suddenly changing to be frightening religion. The destruction in some places such as Bali Bombing, JW Marriot Bombing, and Sampang riot in some places Islam is the trigger of religious violence. This paper discusses the repetition of religious violence in Indonesia especially after New Order era. The writer argues that religious violence in Indonesia is as natural disaster, historical process in human evolution and as close experience that presenting and relating to human history. It may be caused by political condition and the response to economic injustice. In doing so, it is kind of social acceleration toward the process of change and also being a factor of the emergence of new agenda. This is because every disaster, including religious violence, requires an adjustment and a new formulation of the functions that have been damaged.